Studies of Biosorption of Heavy Metals in Soil by Using Rice Straw - Mazher, Farhana; Ghaffar, Abdul; Arooj, Ammara; Iqbal, Mudassara (Asian Journal of Chemistry, 2012)
Adsorption experiments were carried out using waste rice straw as a biosorbent to adsorb Cd, Pb, Cr, Co, Ni and Cu at room temperature from agricultural soil irrigated with industrial waste water. Estimation of metals was done by atomic absorption spectroscopy. The main objective was to determine (I) appropriate adsorption isotherm of heavy metals and (II) adsorption efficiency of heavy metals on rice straw. Metal removal efficiency of rice straw was observed after 8 and 30 days by varying the amount of biosorbent. Eight days equilibrium studies showed that Langmuir isotherm provided the best correlation for Ni, Cu and Co while after 30 days the studies gave the Langmuir isotherm correlation with Cd, Pb. Ni and Cr. Similarly Pb, Cd, Cu, Co and Cr followed Freundlich isotherm. Nickel had highest adsorption capacity on to rice straw. Estimation of nitrates, sulphates and phosphates were done by using UV-Visible spectrophotometer. X-ray diffraction studies were also done, which indicates the presence of SiO2 and Muscoit mineral.